(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Traditional construction methods commonly produce waste and contribute to the environment’s pollution. This study aims to develop a framework that will integrate green building techniques into the construction sector. The Analytical Network Process (ANP) and Zero One Goal Programming(ZOGP) were used to lead the overview .The outcomes recommended a decent arrangement to accomplish a practical green reliance system; this incorporates numerous mediations that can be utilized to move customary development to green development. The review reasoned that voyaging greenlings are more affordable whenever utilized effectively. The results of the survey indicated that a good plan should be developed to implement a green dependence framework. This framework should include various interventions that can help minimize the cost of green construction. Doing business around can save you time and money while improving the safety and cleanliness of buildings. It is also a good idea to consider new forms of energy and water conservation. It can also help minimize energy use and costs. It can also help avoid costly mistakes and doing so can also help minimize air pollution.